Tumor Angiogenesis - Farah Fatma Wati; Whendy Wijaksono (Jurnal Respirasi, 2018)
Tumor angiogenesis, a process in which blood vessels penetrate and grow in a tumor environment, is needed for oxygen and nutrient supply and plays an important role in the survival of solid neoplasms. Angiogenesis does not only have a role in tumor development and metastasis, but also acts as marker of cancer itself (hallmark of cancer). Several mechanisms of angiogenesis include vasculogenesis, sprouting angiogenesis, intussusception microgrowth, and vasculogenic mimicry. Knowing these different mechanisms will be helpful in choosing the best agents or drugs for cancer therapy. The first anti-angiogenic drug used was bevacizumab, a monoclonal antibody, directed against VEGF. Bevacizumab has significant clinical benefits in patients with advanced NSCLC.